2012
DOI: 10.1016/j.resuscitation.2012.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of acetate-balanced colloid and crystalloid resuscitation on renal oxygenation in a rat model of hemorrhagic shock

Abstract: While resuscitation with the NaCl and RA (crystalloid solutions) and the HES-NaCl (unbalanced colloid solution) led to hyperchloremic acidosis, resuscitation with the HES-RA (acetate-balanced colloid solution) did not. The HES-RA was furthermore the only fluid restoring renal blood flow back to ∼85% of baseline level and most prominently improved renal microvascular oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Because crystalloids (e.g., LR) are poor plasma expanders, 80% of the given volume would have shifted into the extracellular space (Almaca et al, 2012). The shift from the intravascular space can be aggravated by endothelial injury, capillary leakage, and accumulating extracellular edema, all of which are common pathophysiological mechanisms during hemorrhagic shock (Ertmer et al, 2011) In our 3:1 group, we observed pulmonary interstitial fluid accumulation, which led to an increase in the EVLWI and lung wet weight:dry weight ratios, and consequently a decrease in PaO 2 compared with the 1:3 group and the baseline value.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because crystalloids (e.g., LR) are poor plasma expanders, 80% of the given volume would have shifted into the extracellular space (Almaca et al, 2012). The shift from the intravascular space can be aggravated by endothelial injury, capillary leakage, and accumulating extracellular edema, all of which are common pathophysiological mechanisms during hemorrhagic shock (Ertmer et al, 2011) In our 3:1 group, we observed pulmonary interstitial fluid accumulation, which led to an increase in the EVLWI and lung wet weight:dry weight ratios, and consequently a decrease in PaO 2 compared with the 1:3 group and the baseline value.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, 6% HES 130/0.4 is a kind of saline-based colloid solution, whereas LR is a balanced crystalloid solution. Although saline-based solutions have been associated with disturbed acid-base balance because of their non-physiological electrolyte composition and pH (Wilcox, 1983;Scheingraber et al, 1999), they remain to be popular choices for volume replacement therapy in perioperative care (Almaca et al, 2012). In addition, saline-based solutions are known to be more frequently associated with hyperchloremic acidosis, owing to their high levels of chloride, resulting in renal vascular constriction and potentially to renal dysfunction (Williams et al, 1999;Brill et al, 2002;Almaca et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main causes of death secondary to hemorrhagic shock are tissue hypoperfusion, major bleeding, and reperfusion injury, which can lead to multiple organ dysfunction syndrome. [8][9][10][11][12] Hemorrhagic shock is characterized by tissue hypoperfusion caused by a sharp reduction in the effective circulating volume of blood. Therefore, the key to successful resuscitation lies in eliminating the shock as soon as possible while simultaneously restoring blood perfusion to the bilateral common carotid arteries, if the liquid is infused through one side of the common carotid artery, the infusion will not cause reduction in blood flow to the brain because of the compensation from the other side.…”
Section: Introductionmentioning
confidence: 99%